2011
DOI: 10.1111/j.1600-0501.2011.02283.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensation and maximum bite force in edentulous patients rehabilitated with bimaxillary implant‐supported fixed dental prostheses

Abstract: Objective: The aim of this study was to compare tactile sensitivity and maximum voluntary bite

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…Thus, apart from denture bending moments the impact of individual occlusal forces and the closing pressure should be discussed as causative factors for veneering problems and acrylic tooth fractures. Considering the type of opposite jaw dentition, retentions of the synthetic veneerings should be fabricated individually or possibly reinforced for avoiding potential fractures …”
Section: Discussionmentioning
confidence: 99%
“…Thus, apart from denture bending moments the impact of individual occlusal forces and the closing pressure should be discussed as causative factors for veneering problems and acrylic tooth fractures. Considering the type of opposite jaw dentition, retentions of the synthetic veneerings should be fabricated individually or possibly reinforced for avoiding potential fractures …”
Section: Discussionmentioning
confidence: 99%
“…Figure A shows the load to failure values obtained on the prototypes as a function of the surface treatments conducted. They are compared to publically available data for other ceramic (3Y‐TZP‐based) implants . Values are similar irrespective of the surface treatments, ranging from 336 N in average after machining down to 286 N following sandblasting, etched and then annealed prototypes in which residual machining/sandblasting stresses were relieved.…”
Section: Potential Applications Of Ductile Ceramics: Case Study On Immentioning
confidence: 97%
“…Such control is needed for refinement and control of the biting force for various types of food [7, 3032]. While patients with implant-supported bridges are able to bite food with varying levels of hardness, it could be questioned whether they are able to differentiate between the hardness variations and thus apply an adapted chewing pattern [33]. Although some studies have demonstrated the tactile function of patients with oral implants [18, 19], the perception of food hardness is yet another sensory function that should be evaluated in order to obtain more information on modulation and masticatory adaptation.…”
Section: Introductionmentioning
confidence: 99%